Application of triple-layer remote phosphor configuration results in the color quality and luminous efficiency enhancement of WLEDs - Thuc Minh Bui; Phan Xuan Le; Dinh Hoang Bach; Nguyen Doan Quoc Anh (Universitas Ahmad Dahlan, 2019)
This study proposed the triple-layer remote phosphor (TRP) structure to enhance the color quality and the emitted luminous flux of white LEDs (WLEDs). The TRP structure consists of three different phosphor layers that are arranged as follows: the yellow YAG:Ce3+ phosphor at the bottom, the red phosphor layer CaMgSi2O6:Eu2+,Mn2+ at the top and the green Ba2Li2Si2O7:Sn2+,Mn2+ phosphor between these two ones. The aim to use the red CaMgSi2O6:Eu2+,Mn2+ phosphor is to control the red light component so that the color rendering index (CRI) could be increased. While the green Ba2Li2Si2O7:Sn2+,Mn2+ phosphor is applied to manage the green light component, leading to the rise in luminous efficacy (LE) of WLEDs. Moreover, when the concentrations of these two phosphors are raised, that of the yellow phosphor YAG:Ce3+ has to be decreased to remain the average correlated color temperatures (ACTTs) in a range from 6000 K to 8500 K. Furthermore, not only the CRI and LE but the color quality scale (CQS) is also analyzed by controlling the two green and red phosphor concentrations. The researched results show that the higher the concentration of CaMgSi2O6:Eu2+,Mn2+, the more enhancements in the CRI will be made. In contrast, when the Ba2Li2Si2O7:Sn2+,Mn2+ concentration increases, the CRI significantly decreases. Meanwhile, CQS is likely to considerably rise in a concentration range from 10% to 14% of CaMgSi2O6:Eu2+,Mn2+, regardless of the presence of Ba2Li2Si2O7:Sn2+,Mn2+ concentration. Especially, in parallel with the improvement of CRI and CQS, the LE could be also increased by more than 40% due to the decline in back-scattering lights and the green lights supplement. From these details, the results of this study are valuable references for manufacturers to achieve the goals of enhancing color quality and luminous efficiency of WLEDs.